2020
DOI: 10.17352/2455-5479.000099
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control and its associated factors among hypertensive patients in federal teaching hospital, ido- ekiti, Southwest Nigeria

Abstract: Background: Hypertension is a modifi able risk factor for cardiovascular disease, stroke and renal disease worldwide. Despite improvement in treatment modality and therapeutic intervention, with proven benefi ts in reducing the burden of uncontrolled hypertension, majority of peoples' blood pressure still remain uncontrolled. Aim: To assess the patterns of blood pressure control and its associated factors among hypertensive patients on follow-up. Setting: This study was done at the general outpatient departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Respondents recruited from the cardiology medical outpatient clinics are more likely to have various cardiovascular complications as well as other causes of secondary hypertension which might make blood pressure control more difficult. Other local studies reported a higher control rate of 53.3% compared to ours [7,26]. A striking finding in this study was the high prevalence of uncontrolled blood pressure among the study participants attending the Cardiology outpatient clinic which underscores the need to emphasize and probably evolve more effective strategies, even amongst specialist Cardiologists, specifically targeting optimal blood pressure control among patients with hypertension.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Respondents recruited from the cardiology medical outpatient clinics are more likely to have various cardiovascular complications as well as other causes of secondary hypertension which might make blood pressure control more difficult. Other local studies reported a higher control rate of 53.3% compared to ours [7,26]. A striking finding in this study was the high prevalence of uncontrolled blood pressure among the study participants attending the Cardiology outpatient clinic which underscores the need to emphasize and probably evolve more effective strategies, even amongst specialist Cardiologists, specifically targeting optimal blood pressure control among patients with hypertension.…”
Section: Discussionmentioning
confidence: 42%
“…Reasons for poor drug adherence are multiple and may be mostly due to medication cost, pill burden, medication unavailability, and depression amongst others. Ezeala et al [27] reported high depression scores, low disability scores and presence of co-morbidities such as peptic ulcer disease significantly correlated with nonadherence to antihypertensive medications. A similar study conducted in Ethiopia [25] reported a low prevalence (11.4%) of nonadherence compared to our finding, however, the study included participants with co-morbidities such as diabetes mellitus, which probably enhanced adherence in their patients for fear of developing more severe cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation